Social work perspectives on human behaviour - Parrish, Margarete (Open University Press, 2010)
By drawing from biological, psychological and sociological perspectives, the book aims to provide social work students with a theoretically informed basis to observe, understand, and interpret people's behaviours in ways that will contribute to excellent practice.